2022
DOI: 10.1080/13614533.2022.2039244
|View full text |Cite
|
Sign up to set email alerts
|

Factors Shaping Future Use and Design of Academic Library Space

Abstract: COVID is having immediate and long-term impacts on the use of library space through social distancing and shifts in how campus space is used. But these changes will probably not alter the importance of the academic library as a space. In the decade pre COVID libraries saw a growing number of visits, despite the increasing availability of material digitally. The first part of the paper offers an analysis of the main factors driving this historic growth, such as changing pedagogies, diversification in the studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…Also, Nawarathne and Singh (2012) also found that user satisfaction with library design is crucial for academic libraries, and understanding www.afropolitanjournals.com user needs and continuously improving infrastructure are key factors in enhancing satisfaction levels among library users. Moreso, the research findings are contrary to that of Cox (2023) the study found that factors influencing library design include changing pedagogies, student diversity, technology, estates management, staff readiness, cost, decision-making speed, student well-being, sustainability, equality, diversity, inclusion, co-design with students, and new technologies. Also, Osłowska (2022) found that technologies, materials, and current trends influence contemporary library design, shaping multifunctional spaces that evoke positive emotions and promote dialogue and experiences among users, enhancing urban environments.…”
Section: Methodscontrasting
confidence: 75%
“…Also, Nawarathne and Singh (2012) also found that user satisfaction with library design is crucial for academic libraries, and understanding www.afropolitanjournals.com user needs and continuously improving infrastructure are key factors in enhancing satisfaction levels among library users. Moreso, the research findings are contrary to that of Cox (2023) the study found that factors influencing library design include changing pedagogies, student diversity, technology, estates management, staff readiness, cost, decision-making speed, student well-being, sustainability, equality, diversity, inclusion, co-design with students, and new technologies. Also, Osłowska (2022) found that technologies, materials, and current trends influence contemporary library design, shaping multifunctional spaces that evoke positive emotions and promote dialogue and experiences among users, enhancing urban environments.…”
Section: Methodscontrasting
confidence: 75%
“…In common with the United Kingdom and other countries [25], libraries will be required to provide possible support for the improvement of students' mental health.…”
Section: Expanded Provision Of Academic Research Materialsmentioning
confidence: 99%
“…Innovative Spaces. the creation of collaborative spaces [5] and unplugged areas [13] where interaction and creativity can occur including the use of games to teach learning concepts [35]. The availability of Open-source architecture for educational research laboratories for concurrent experiments, connected clients, and other use cases like VR and smart environments may also be employed [40].…”
Section: Data Gathered From Research Gaps and Research Recommendationsmentioning
confidence: 99%
“…Green libraries are libraries that prioritize environmentally sustainable practices in their operations and services such as reducing energy consumption, using renewable energy sources, promoting recycling and waste reduction, purchasing environmentally friendly products, and offering educational programs and resources on environmental issues. Rethinking how library operations affect the environment is necessary [5]. In fact, sustainability, and climate change [4] are among the global issues that libraries should engage in to ensure that programs and activities are eco-friendly.…”
Section: Data Gathered From Research Gaps and Research Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation